Approaching Cognitive Behavior Therapy For Generalized Anxiety Disorder From A Cognitive Process Perspective - Hirsch, Colette R.; Beale, Sarah; Grey, Nick; Liness, Sheena (Frontiers in Psychiatry, 2019)
Generalised anxiety disorder (GAD), with uncontrollable worry at its core, is a common psychological disorder with considerable individual and societal costs. Cognitive behaviour therapy (CBT) is recommended as the first-line treatment for GAD; however, further investigation into its effectiveness in routine clinical care is indicated and improvement is required in treatment outcomes for worry. Improvements to CBT need to be guided by experimental research that identifies key mechanisms maintaining core aspects of the disorder. This paper summarises how theory-driven experimental research guided selection and refinements of CBT techniques originally developed by Borkovec and Costello (1993), to target key cognitive processes that maintain worry in GAD. Hirsch and Mathews’ (2012) model specifies three key research-supported processes that maintain uncontrollable worry in GAD: implicit cognitive biases such as negative interpretation bias and attention bias, generalised verbal thinking style, and impaired ability to re-direct attentional control away from worry. Specific CBT techniques outlined in this paper aim to target these key processes. Clinical data from clients treated using our refined CBT protocol for GAD in a routine clinical care service with a special interest in anxiety disorders were collected as part of service procedures. Large pre-to-posttreatment effect sizes were obtained for anxiety (GAD-7), depression (PHQ-9), and worry (PSWQ) (d=.90-2.54), and a moderate effect size was obtained for quality of life (WASA; d=.74). Recovery was indicated for 74% of cases for anxiety, 78% for depression, and 53% for worry. These findings exceeded most previous effectiveness studies in routine care and were in-line with GAD efficacy trials. This paper also outlines the application of specific clinical techniques selected, adapted or developed to target key cognitive mechanisms which maintain worry in GAD.